Education as a Catalyst of Personality Development: A Case Study of ‘Omar bin Khattāb (R.A) - Qureshi, Hafsah Ayaz; Bukhari, Syed Abdul Ghaffar (Journal of Islamic and Religious Studies, 2019)
The individual’s personality, character, thinking, skills and habits depends upon education. Education helps in the growth and boost the qualities of an individual such as physical, mental and emotional make-up as well as temperament and character. This paper enlightens the significant role of education in developing and mounting the personality of ‘Omar Ibn alKhattāb (R.A). He was one of the most powerful and influential Muslim caliphs. His vibrant ideology of superiority of principles and laws made him eminent among his acquaintances. He was a man of determination and a mission, therefore, he thought, evaluated and acted according to it. He established a system of justice, morality, education and training. He was born as an ordinary‘Omar but education and guidance of Islam made him “‘Omar The Great”. This paper ends with the note that a balanced, successful and well-adjusted personality can be designed only by educating the individuals. Educational institutions, religious organizations and enrich culture play an important role in shaping the sturdy personality as is evident in case of ‘Omar(R.A).